ANALISIS PENGGUNAAN AIR DISTILASI SEBAGAI MEDIA PENYERAPAN EMISI NOX PADA GAS BUANG SEPEDA MOTOR HONDA SUPRA X 125 TAHUN 2012 - Setyawan, Budhi (Jurnal Nosel, 2014)
Purposes of the research are: (1) to know effect of distilled-water use as an absorptive media on NOx emission of exhaust gas of motorcycle Honda Supra X 125 2012, and (2) to know effect of distilled water surface height on absorption of NOx emission of exhaust gas of motorcycle Honda Supra X 125 2012. The research was an experimental method. Data analysis of the research was descriptive comparative analysis. Descriptive research method aims to describe and to interpret existing data attempting to seek problem solving through causal relationship, namely to examine particular factors related to investigated-situation or phenomenon and to compare one factor to another (Surakhmad, 1998: 139, 143). Results of the research conclude that: (1) there has been a decrease of NOx after the use of distilled water as an absorptive media of exhaust gas. Emission level of NOx without distilled water is greater than that of with distilled water. Mean difference between NOx emission without distilled water and one with distilled water at water surface height of 200 mm is 1.65 ppm. While, mean difference of NOx emission with water surface of 200 mm and that of 400 mm is 0.42 ppm. Further, for water surface height of 400 mm and 600 mm, the mean difference is 0.44 ppm; (2) there is effect of water surface height on power of absorbing NOx emission of exhaust gas. The higher distilled water surface height, the longer period of time the exhaust gas contact with water so that water-soluble NOx emission level is greater also. For water surface height of 400 mm, mean emission of NOx is 11.00 ppm and for water surface height of 600 mm, mean NOx emission is 10.56 ppm.